Pengaruh Coretax dan Sanksi Perpajakan terhadap Kepatuhan Pajak pada Credit Union dimoderasi Sistem Pengendalian Manajemen - Roziana, Roziana; Risal, Risal; Afif, Ali (TIN: Terapan Informatika Nusantara, 2025)
The main source of state revenue is taxes, but corporate taxpayers' compliance with Credit Unions (CU) of Puskopcuina members is still low. This study analyzes the influence of Coretax implementation and tax sanctions on compliance, with the Management Control System (SPM) as moderation. The study used a quantitative approach involving 47 respondents, where data was collected through questionnaires and analyzed using SPSS 26 through data quality tests, classical assumption tests, descriptive analysis, and hypothesis tests. The results showed that the implementation of Coretax had no significant effect on compliance (coefficient of 0.034; significance of 0.839), while tax sanctions had a significant positive effect (coefficient of 0.284; significance of 0.047). SPM weakened the influence of Coretax (coefficient of -0.149; significance 0.020) and strengthened the influence of tax sanctions (coefficient of 0.149; significance 0.009). Thus, tax sanctions play an important role in encouraging increased compliance of corporate taxpayers, while the effectiveness of Coretax is highly dependent on MCS support.